Sadari Penyakit Gout dan Gangguan Metabolik melalui Deteksi Dini Kadar Asam Urat di Sekolah Kalam Kudus 2, Jakarta - Emilda, Emilda; Santoso, Alexander Halim; Destra, Edwin; Teguh, Stanislas Kotska Marvel Mayello; Jap, Ayleen Nathalie (Lembaga Pengembangan Kinerja Dosen, 2025)
Hyperuricemia is a condition of increased uric acid levels in the blood that can develop into various metabolic disorders, including gouty arthritis and kidney disease. Physical activity is known to play an important role in controlling uric acid levels by increasing excretion and inhibiting purine production. This activity uses the Plan-Do-Check-Act (PDCA) approach which includes checking uric acid levels using the Point-of-Care Testing (POCT) method in 91 productive-age individuals, as well as education about the importance of physical activity. The results were obtained directly and presented to the participants along with interpretive explanations and preventive recommendations. The average uric acid levels of the participants were recorded at 3.78 ± 0.60 mg/dL with a range of 2.5 to 5.6 mg/dL. All participants (100%) had uric acid levels within the normal range. Physical activity contributes to the regulation of uric acid levels, so proper education remains important even though the examination results show normal values. Education-based interventions play a role in strengthening primary prevention.